2013
DOI: 10.1155/2013/512978
|View full text |Cite
|
Sign up to set email alerts
|

Long Course Hyperbaric Oxygen Stimulates Neurogenesis and Attenuates Inflammation after Ischemic Stroke

Abstract: Several studies have provided evidence with regard to the neuroprotection benefits of hyperbaric oxygen (HBO) therapy in cases of stroke, and HBO also promotes bone marrow stem cells (BMSCs) proliferation and mobilization. This study investigates the influence of HBO therapy on the migration of BMSCs, neurogenesis, gliosis, and inflammation after stroke. Rats that sustained transient middle cerebral artery occlusion (MCAO) were treated with HBO three weeks or two days. The results were examined using a behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 48 publications
(58 reference statements)
4
59
0
Order By: Relevance
“…Ischemic stroke is induced by cerebral artery occlusion, which can cause regional cerebral flow reduction or interruption (1). The brain is sensitive to ischemia, the effect of which may be exacerbated by the reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke is induced by cerebral artery occlusion, which can cause regional cerebral flow reduction or interruption (1). The brain is sensitive to ischemia, the effect of which may be exacerbated by the reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Opposite results were also found in some previous experiments for several hours after ischemia-reperfusion by using HBO therapy [50,51] . Recently, a new study [52] has testified that HBO might attenuate inflammation in transient MCAO rats with a long-course schedule (3 weeks or 2 days after MCAO, repeated for 3 weeks). This point has also been reflected in the HBO therapy of traumatic brain injury [53] .…”
Section: Hbo Alleviates Inflammationmentioning
confidence: 99%
“…Simultaneously, studies have shown that the positive effects still exist in brain damage [75] and spinal cord injury [76] . Long-course and repeated HBO therapy for cerebral ischemia can also generate similar outcomes [52,77] .…”
Section: Hbo Inhibits Apoptosis and Neuroprotective Effectsmentioning
confidence: 99%
See 2 more Smart Citations